ANALYSIS OF FULL-FACTOR EXPERIMENTAL STUDIES OF A COTTON CLEANER - Abdialim Tukhliev; Alisher Abdusamatov; Shakhnoza Khaytbaeva (Galaxy International Interdisciplinary Research Journal, 2021)
The article presents the results of full-factor experimental researches of a cleaning machine with a new design of the feeder. The dependences of cotton cleaning efficiency on the relative speed of the feed rollers, on the productivity of the machines and the effect of changes in the gap between the feed rollers are given. The optimal parameters of input factors are recommended.